2018
DOI: 10.1007/s12602-018-9413-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Feed-Supplementation with Probiotic Strain Lactobacillus reuteri CCM 8617 and Alginite on Intestinal Microenvironment of SPF Mice Infected with Salmonella Typhimurium CCM 7205

Abstract: Alginite is a non-ore raw material arising by fossilization of accumulated organic (algae) and inorganic material, particularly clay, carbonates, quartz, and amorphous modification of silicic acid in the aqueous environment. Humic acids as a component of organic portion of alginite are known for very good buffering ability which allows them to stabilise pH throughout the digestion system of animals, stimulate receptors of the immune system in intestinal villi against pathogenic bacteria, and support proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…strains lead to the accumulation of SCFAs, such as acetic acids and butyrate (55)(56)(57). A previous study conducted by Gancarčíková et al confirmed that the increase in the caecal SCFA concentrations (mainly in the butyric, acetic, and propionic acid concentrations) was induced by L. reuteri (58). In the present study, the BLF supplementation increased the relative abundance of L. acidophilus, L. gasseri, and L. reuteri compared to the Anti treatment, as well as the relative abundance of L. reuteri compared to the control treatment.…”
Section: Effects Of Dietary Blf On Caecal Scfasmentioning
confidence: 85%
“…strains lead to the accumulation of SCFAs, such as acetic acids and butyrate (55)(56)(57). A previous study conducted by Gancarčíková et al confirmed that the increase in the caecal SCFA concentrations (mainly in the butyric, acetic, and propionic acid concentrations) was induced by L. reuteri (58). In the present study, the BLF supplementation increased the relative abundance of L. acidophilus, L. gasseri, and L. reuteri compared to the Anti treatment, as well as the relative abundance of L. reuteri compared to the control treatment.…”
Section: Effects Of Dietary Blf On Caecal Scfasmentioning
confidence: 85%
“…A limited number of studies have reported that valeric acid may stimulate intestinal growth and ameliorate the pathogenesis of diseases ranging from colitis and cancer to cardio-metabolic diseases [48,49,50]. Moreover, a variety of animal and human studies have reported very low to undetectable concentrations of valeric acid in faeces, colon, cecum, and ileum [51,52,53,54]. Interestingly, in the present study, valeric acid levels were clearly detected and upregulated among mucosal samples in both DDS-1 treated groups and were positively correlated with an increase in Bacteroidetes level [52].…”
Section: Discussionmentioning
confidence: 99%
“…Leonardite is rich in humic acids, and due to its macrocolloid structure can protect intestinal mucosa by reducing the resorption of toxic metabolites from the residues of harmful substances in feed [25]. Humic acids prevent an excessive loss of water from the gut, which is important in the treatment of diarrhoea, dyspepsia, and acute intoxications [26].…”
Section: Introductionmentioning
confidence: 99%